Awakening sensations: multisensory art experiences to learn to connect with childhood (Revista Apotheke, 2024)
“Awakening Sensations” offers a set of proposals that, starting from the sensory stimulation of various senses, activates cognitive processes of recognition, memory, and perception that transcend the mere sense of sight as a receiver and generator of information. The aim is for future preschool teachers to learn to work with different senses, thus expanding their training comprehensively to capitalize on the perceptual and expressive possibilities that children offer them according to their age. This type of experience helps break stereotypes and prejudices related to the shape, appearance, and color of things, as well as the perception that students have of their own performance and artistic abilities.
Keywords: multisensoriality; sensory experiences; artistic expression; early childhood sensory education